How Is The Student's Numeracy Ability During Learning In The Pandemic Era? - Umar Umar; Arif Widodo (Jurnal Scientia, 2021)
Numeracy is an important skill that must be mastered by students. Almost all human activities are related to numbers. The existence of numbers cannot be separated from everyday life. Numbers are so important since elementary school students are always taught numbers. The problem is during the pandemic with the threat of learning loss, does it affect students' numeracy skills? This study aims to determine the profile of school students' abilities in the field of basic numeracy during the Covid-19 pandemic. The research used a survey method. Collecting data using a numerical test. The research location is at SDN Lingkok Lima. The research subjects are 110 students. Data were analyzed using descriptive statistics. The data is presented in the form of tables and diagrams. The findings from the results of the study are that students' numeracy skills are low. Many students are found who are not able to read four-digit numbers, determine place values ​​and perform basic arithmetic operations